PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS PENDIDIKAN MATEMATIKA REALISTIK PADA MATERI PLSV KELAS VII SMP - LESTARI, NURUL ITA (Universitas Pasir Pengaraian, 2016)
AbstractThis research was development. This study aims to develop and know the quality of studentâs worksheet (lembar kerja siswa) based Realistic Mathematics Education (RME) on Linier Equation One Variable VII grade Junior High School based aspect of validity and practicality. This research used of model 4-D, but in this research was limited to 3-D stage comprising the steps of defining, design and development. The subjects were students VII grade at SMP N 8 Tambusai Utara. The instrument used to measure the quality of products were the validation sheet worksheets, the questionnaires of practicalities expert, the questionnaire of teacherâs responses, and the questionnaire of studentâs responses. Studentâs worksheet (lembar kerja siswa) based Realistic Mathematics Education developed was met criteria very valid according to the validator with average score about 3.43. Studentâs worksheet (lembar kerja siswa) based Realistic Mathematics Education developed was met criteria practic based on the questionnaires of practicalities expert with the average value 81.67% and based on the questionnaire of teacherâs responses with the average value 84.09%. While based on the questionnaire of studentâs responses, studentâs worksheet (lembar kerja siswa) based Realistic Mathematics Education developed was met criteria very practic with the average value 86.42%.